PENERAPAN PRINSIP BERKELANJUTAN SEBAGAI UPAYA PENCEGAHAN KERUSAKAN LINGKUNGAN HIDUP DIBIDANG PERTAMBANGAN DITINJAU DARI U-U NOMOR 4 TAHUN 2009 - Karel ., Wowor (Sam Ratulangi University, 2017)
This literature study aims to determine the application of the principle of sustainable development as an effort to prevent environmental damage in the field of mining in terms of Law No. 4 of 2009. Data collection methods used in this literature study, as the material for analysising, using the following methods: (1 ) Research specifications. The type of legal research conducted in answering the problems is normative legal research with the consideration that the starting point of analysis research on the application of sustainable development principles to the laws and regulations of the field of mineral and coal mining. Normative legal research is a literature assessment, so the research used secondary data. (2) Research Data. Materials in this research are taken from secondary data consisting of: (a) Primary legal materials, namely binding legal materials and consist of: (i) the Constitution of the Republic of Indonesia Year 1945; (ii) Law No. 4 of 2009 on Mineral and Coal Additions and (iii) Law No. 32 of 2009 on Environmental Protection and Management. (b) Secondary legal substances, ie legal materials that provide explanations of primary legal materials, such as the Draft Law, the opinions of legal experts. (c) Tertiary legal substances, which provide guidance as well as explanations of the primary and secondary legal materials which include such as the Law Dictionary, Indonesian Dictionary, and English Dictionary. (3) Data collection techniques. Collecting data from the writing of this research is done through literature research, a series of efforts to obtain data and facts by way of reading, reviewing, clarifying, identifying and understanding about legal materials in the form of laws and regulations as well as books, literature books, articles, journals, and other sources of relevance to the research problem. The research results show that the company's responsibility in the management of natural resources and the environment is linked to the principle of sustainable development differentiated between social responsibility and absolute responsibility. Social responsibility includes corporate social responsibility programs (CSR). While the absolute responsibility emphasizes that the company should manage the natural resources properly and can be absolutely required accountability in case of damage to the environment. In such a management, coordination and partnership with related parties should be carried out in order to achieve integration and synchronization between economic, social, and environmental. Corporate social and environmental responsibilities should apply some principles of sustainable development, namely: Principles of intergenerational justice, principles of intragenerational justice, principles of early prevention, principles of biodiversity protection, Principles of internalization of environmental costs. Principle, sustainable development as an effort to prevent environmental damage in the field of mining in view of Law No. 4 of 2009 on Mineral and Coal Mining has been implied in several articles in this law. Sustainability in mining does not mean that the activity can be done continuously. In Article 2 and 3 of the Constitution Act of Minerba, it states that there are alignments to the national interest and the principles of sustainability and environmental insight (eco-vision).